2008
DOI: 10.1002/ibd.20375
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular and functional changes in colonic epithelium that precede increased gut permeability during colitis development in mdr1a(−/−) mice

Abstract: These studies show that early epithelial changes associated with altered responsiveness to bacteria precede increased permeability and mucosal inflammation in this model of colitis, highlighting the importance of P-glycoprotein in regulating interactions with the commensal microflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…We now demonstrate that prophylaxis with this TLR2 ligand prevents spontaneous onset of chronic colitis. Pathogenesis of commensaldriven pancolitis in FVB/N mice deficient in MDR1␣ gene expression involves primary IEC barrier dysfunction associated with alterations in interferon ␥-responsive genes in the lamina propria (43)(44)(45)(46). Despite presence of CC-chemokines and proinflammatory interferon ␥ in the mucosal milieu, which disrupt Cx43 (11,58), treatment with PCSK suppressed inflammatory induced accumulation, Ser 368 phosphorylation, and morphological disruption of Cx43 in intestinal epithelial cells in parallel with delayed onset of mucosal disease.…”
Section: Discussionmentioning
confidence: 99%
“…We now demonstrate that prophylaxis with this TLR2 ligand prevents spontaneous onset of chronic colitis. Pathogenesis of commensaldriven pancolitis in FVB/N mice deficient in MDR1␣ gene expression involves primary IEC barrier dysfunction associated with alterations in interferon ␥-responsive genes in the lamina propria (43)(44)(45)(46). Despite presence of CC-chemokines and proinflammatory interferon ␥ in the mucosal milieu, which disrupt Cx43 (11,58), treatment with PCSK suppressed inflammatory induced accumulation, Ser 368 phosphorylation, and morphological disruption of Cx43 in intestinal epithelial cells in parallel with delayed onset of mucosal disease.…”
Section: Discussionmentioning
confidence: 99%
“…For both models of experimental colitis, it has been shown that levels of IFN-␥ are elevated (6,7). Colonic tissues from C57BL/6 mice subjected to acute DSS colitis showed a significant increase in EGFr expression compared with tissues from control C57/BL6 mice (Fig.…”
Section: Experimental Colitis Induces Opposing Effects On Egfrmentioning
confidence: 91%
“…Indeed, IFN-␥ Ϫ/Ϫ mice are resistant to DSS-induced colitis (5). In another model of spontaneous colitis, the mdr1a Ϫ/Ϫ mouse, IFN-␥ mRNA and protein levels are elevated more than 50-fold in mice with established colitis compared with controls, and production of IFN-␥ is also elevated in stimulated mesenteric lymph nodes (6,7). Interestingly, the human MDR gene is located on chromosome 7, a susceptibility locus for inflammatory bowel diseases (8).…”
mentioning
confidence: 99%
“…However, it has been shown that MDR1 interferes with bacterial adhesion to enterocytes and reduces the risk of gastrointestinal disorders (15). Interestingly, at the same time, mdr1a-/-mice display reduced expression of regenerating islet-derived protein 3 gamma (REG3G) in intestinal mucosa (32). REG3G prevents exaggerated inflammation by bactericidal activity and suppression of cytokine production (33).…”
Section: Expression Of Cytokines and Socs Moleculesmentioning
confidence: 99%